Innovative Medicine 2015
DOI: 10.1007/978-4-431-55651-0_4
|View full text |Cite
|
Sign up to set email alerts
|

Linear Polyubiquitination: A Crucial Regulator of NF-κB Activation

Abstract: NF-κB is a transcription factor known to be involved in pleomorphic biological phenomena such as infl ammation and immune responses. Abnormal activation of NF-κB has been reported in many pathological conditions, including malignant tumors. Therefore, the NF-κB activation pathway has been extensively studied and involvement of the ubiquitin conjugation system in the NF-κB activation pathways has been revealed. Although the ubiquitin conjugation system was discovered as a part of a protein degradation pathway, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…Emerging experiments have shown that incorrect regulation of cellular processes (either tumour inhibitors or promoters) contributes to cancer pathogenesis and progression ( Shirane et al, 1999 ). Additionally, the cellular functions of atypical ubiquitin linkages (except Lys11-linked ubiquitin) are supposed to be non-degradable ( Kulathu and Komander, 2012 ; Iwai, 2014 , 2015 ; Meza Gutierrez et al, 2018 ) and in most cases, activities involved in Lys63-linked poly-ubiquitin chains are also considered to be non-degradable ( Liu et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…Emerging experiments have shown that incorrect regulation of cellular processes (either tumour inhibitors or promoters) contributes to cancer pathogenesis and progression ( Shirane et al, 1999 ). Additionally, the cellular functions of atypical ubiquitin linkages (except Lys11-linked ubiquitin) are supposed to be non-degradable ( Kulathu and Komander, 2012 ; Iwai, 2014 , 2015 ; Meza Gutierrez et al, 2018 ) and in most cases, activities involved in Lys63-linked poly-ubiquitin chains are also considered to be non-degradable ( Liu et al, 2015 ).…”
Section: Introductionmentioning
confidence: 99%